The development trends, technological competition situations and cooperation status of carbon-negative technology: A patent landscape analysis - Xin Li; Ning Gao; Fei Yuan; Lucheng Huang (Journal of CO2 Utilization)
In the context of carbon neutrality, carbon-negative technology is considered a crucial technology for reducing carbon emissions and achieving carbon neutrality. Carbon-negative technology has gained attention from governments, businesses and academia. To comprehend the overall development status of carbon-negative technology, including the core technologies, the patent landscape, competition, and cooperation among major countries and regions, this paper proposes an analytical framework for the patent landscape of carbon-negative technology. The research results demonstrate the rapid overall development of carbon-negative technology. The R&D strategies of major competing countries in the field of carbon-negative technology focus on specific technology areas, and their core technologies exhibit similarities as well as differences. In the field of technology-based solutions, the United States and China dominate with their leaders and active contributors in various technology domains. The collaboration largely revolves around the United States, while other nations engage in less partnership and interaction. Countries have not yet established technological leadership in carbon sinks technology, and the cooperation network is relatively limited. These findings contribute to our understanding of the current global development status of carbon-negative technology, as well as the competitive levels and positions of major countries in this field. These findings also provide a decision-making basis and support for the development of carbon-negative technology.